Land use transformation and sustainable spatial design lessons from a decade of regional development - Nugrahani, Femi Diah (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: North Tapanuli Regency in North Sumatra has unique characteristics as a region located in the highlands and cool climate, with a dominant wilderness. North Tapanuli is divided into 15 sub-districts, with 11 urban villages and 241 villages. Each sub-district has its own duties, with the capital of the district being in Taruntung. The largest sub-district in North Tapanuli is Adiankoting and the smallest is Sipoholong. Methods: This study employed a qualitative method with a literature review. Findings: In addition to referring to normative regulations referring to the central government and the provincial government, the development of Tapanuli in the ten-year period, namely from 2014 to 2014 was boosted through breakthroughs with the Nikson model or innovation, knowledge, synergy, operation, and norm as a model in regional development planning based on precise data. In one decade, Nikson-style development has reportedly made North Tapanuli Regency a barn for agriculture, fisheries, and forestry. However, this development has changed the spatial layout and environmental quality of North Tapanuli. Conclusion: The North Tapanuli region is still dominated by wilderness. The past ten years have shown significant development, but with the consequence of environmental change. Novelty/Originality of this article: Over time, the population of North Tapanuli has also increased, resulting in land use changes and increased waste volume.